Examination Validation Methodologies for Personnel Certification Schemes - Vural, Osman; Anastasopoulos, Ioannis; Nelson, David (Eximia, 2021)
The validation of the examinations provided by the Conformity Assessment Bodies for Personnel Certification Purposes is a requirement of the international standard ISO/IEC 17024 “Conformity assessment — General requirements for bodies operating certification of persons”. A foundamental requirement for each examination developer is to achieve a reliable and fair examination process. The validity of a test paper depends on the quality of the sections that are constituting the examination. Considering that the examination must measure the competencies derived by the relevant job/task analysis, there is a direct connection between the job/task analysis outputs and the respective examination. There are prescribed steps in linking the relatedness of the examination to the knowledge and skills required for a job. These steps lead to an examination that has been "validated" in that its content accurately measures the necessary knowledge and skill required for the job. This paper describes the steps the examination (personnel evaluation) system should be designed, as well as some of the statistical techniques that can be used in the analysis of items that are necessary for the establishment of question banks. The scope of this paper is limited to the “job analysis” component of certification schemes and does not extend to requirements for administration of examinations, including performance-based assessments, oral examinations, and remote assessments.